A high-throughput 3D bioprinted cancer cell migration and invasion model with versatile and broad biological applicability. (23rd September 2022) - Jung, MoonSun; Skhinas, Joanna N.; Du, Eric Y.; Tolentino, M. A. Kristine; Utama, Robert H.; Engel, Martin; Volkerling, Alexander; Sexton, Andrew; O'Mahony, Aidan P.; Ribeiro, Julio C. C.; Gooding, J. Justin; Kavallaris, Maria
Abstract : A HTP 3D bioprinted cell migration platform that has broad applications across quantitative cell and cancer biology as well as drug screening. Abstract : Understanding the underlying mechanisms of migration and metastasis is a key focus of cancer research. There is an urgent need to develop in vitro 3D tumor models that can mimic physiological cell–cell and cell–extracellular matrix interactions, with high reproducibility and that are suitable for high throughput (HTP) drug screening. Here, we developed a HTP 3D bioprinted migration model using a bespoke drop-on-demand bioprinting platform. This HTP platform coupled with tunable hydrogel systems enables (i) the rapid encapsulation of cancer cells within in vivo tumor mimicking matrices, (ii) in situ and real-time measurement of cell movement, (iii) detailed molecular analysis for the study of mechanisms underlying cell migration and invasion, and (iv) the identification of novel therapeutic options. This work demonstrates that this HTP 3D bioprinted cell migration platform has broad applications across quantitative cell and cancer biology as well as drug screening.